RESEARCH OF PASSENGER TRAFFIC IN PUBLIC TRANSPORT OF THE CITY OF URGENCH - Omarov J. A. (Galaxy International Interdisciplinary Research Journal, 2022)
As a result of the acceleration of the urbanization process, the increase in megacities, population growth, the demand and need for public transport are increasing every year. This, in turn, leads to the need to improve the efficiency of public transport, adapt to today's times and conditions. This determines the importance of increasing the efficiency of using the existing transport infrastructure through proper planning and modeling of urban public transport. The article describes the methodology for determining passenger traffic on existing public transport routes (using the example of the city of Urganch).